Phase behavior and pH modelling for ammonia-MEA-water mixtures for corrosion control in water utility applications - Ratnakar, Ram; Gupta, Somil S.; Stockinger, Georg; Hamer, Wouter; Dindoruk, Birol (Fluid phase equilibria, 2022)
•Fluid mixture containing H2O-NH3-MEA is characterized by a non-classical EOS model.•A predictive pH model for subject fluid is developed for water utility applications.•The modeling is robust in extended range of pressure, temperature and compositions.•The workflow to obtain safe operating window is discussed for corrosion control.•The methodology is applicable for any aqueous system containing other gases/solutes. We present thermodynamic models for ammonia-MEA-water mixtures and evaluate the pH of the aqueous streams for the purpose of corrosion control in water-utility applications. In particular, (1) An equation of state (EOS) model using Peng-Robinson EOS with the asymmetric Huron-Vidal (HV) mixing rule for aqueous subsystems is developed and calibrated against experimental data; and (2) As an outcome, a modeling workflow is developed to estimate the pH as a function of the temperature and the composition of the aqueous streams. Such studies are important for various chemical and manufacturing industries. Furthermore, the methodologies developed through this work can be applied to wider ranges of pressures and temperatures for water utilities, reactor plants, and refineries. [Display omitted]